MEMBANGUN GROWTH MINDSET MELALUI UMPAN BALIK DESKRIPTIF: STUDI KUALITATIF PADA PEMBELAJARAN FIKIH - Farhaty, Mutiah; Masita; Mulyadin, Wahyu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the dominance of students' fixed mindsets in Islamic jurisprudence (Fiqh) learning, which are dogmatic and focused solely on numerical values. The aim of the research is to explore the implementation of descriptive feedback to develop students' growth mindsets in the Hudud (Islamic Law) material. Using a qualitative case study method, data was collected through participant observation, document analysis, and semi-structured interviews in class XI IPAS 3 of MAN 2 Kota Bima. The results show that providing narratives to improve students' thought processes significantly reduces cognitive anxiety and increases students' confidence in expressing their opinions. In conclusion, descriptive feedback effectively shifts the learning paradigm from merely memorizing legal status to understanding logical-analytical reasoning. This research recommends a shift from absolute numerical assessment to constructive narrative guidance.